2016
DOI: 10.1021/acscatal.6b01755
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity for HCO2 over H2 in the Electrochemical Catalytic Reduction of CO2 by (POCOP)IrH2

Abstract: It has been demonstrated experimentally that electrochemical CO2 reduction catalyzed by (POCOP)­IrH2 ([C6H3-2,6-[OP­(tBu)2]2]­IrH2) produces formate without significant H2. We use first-principles density functional theory (M06) including Poisson–Boltzmann solvation to determine the detailed atomistic mechanism and illuminate strategies for designing formate-selective catalysts. A mechanism involving hydride transfer from IrIII dihydride explains the selectivity for formate over H2 and is corroborated by reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 68 publications
1
39
0
Order By: Relevance
“…4 and 7, respectively) the only two molecular catalysts with >90% selectivity for formate generation function optimally at modest to high pK a /pH conditions, with decreasing selectivity at lower proton activities (16,20). Yet, both maintain fairly high selectivity under more acidic conditions, indicating that the product distribution is also under kinetic control (64).…”
Section: Resultsmentioning
confidence: 96%
“…4 and 7, respectively) the only two molecular catalysts with >90% selectivity for formate generation function optimally at modest to high pK a /pH conditions, with decreasing selectivity at lower proton activities (16,20). Yet, both maintain fairly high selectivity under more acidic conditions, indicating that the product distribution is also under kinetic control (64).…”
Section: Resultsmentioning
confidence: 96%
“…Theoretical calculations by Cao et al. suggested that a moderate hydricity is critical in achieving high selectivity in this system ,. Nozaki et al.…”
Section: Methodsmentioning
confidence: 94%
“…[7] Theoretical calculations by Cao et al suggested that a moderate hydricity is critical in achieving high selectivity in this system. [8,9] Nozaki et al reported iridium complexes of PNP pincer ligands to hydrogenate CO 2 to formate, showing that Ir PNP trihydride complex can insert/de-insert CO 2 reversibly under suitable conditions, [14] thus suggesting that PNP type Ir complex has great potential for reversible electrochemical conversion between CO 2 and formate.…”
Section: Single Iridium Pincer Complex For Roundtrip Electrochemical mentioning
confidence: 99%
“…The free energy of the transition metal hydride intermediate relative to reactants, products and other intermediates, an important thermodynamic quantity that determines the driving force towards hydride transfer to CO 2 and protons to produce HCO 2 À and H 2 respectively, has been well studied as an important descriptor of catalytic activity. [28][29][30][31] For instance, we previously showed, using experimentally calibrated DFT, how specic ligand environments change the free energy of CO 2 insertion into a ruthenium hydride complex. 24 The hydride complex we were studying despite being an active transfer hydrogenation catalyst for ketones 32 was not found to be a catalyst for CO 2 reduction due to product inhibition.…”
Section: Introductionmentioning
confidence: 99%